Analysis the Policy Government of the Republic Indonesia on the Peace Efforts of Palestine and Israel (1988-2024) Siyasah Dauliyah Perspective - Mudaim, Halimah; Saebani, Beni Ahmad; Tresnayadi, Budi (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This research discusses the review of siyasah dauliyah on the role of the Republic of Indonesia in responding and providing policies on the war between Israel and Palestine, one of which is when the war heats up again in 2023. The occurrence of the war has caused enormous destruction in the Palestinian territories ranging from the economic, social, educational sectors, even public facilities, and infrastructures. The research method used the content analysis method with the technique of interpreting textual material and evaluating texts systematically from primary and secondary document data sources. The results showed that Indonesia and Palestine have established diplomatic relations for a long time, starting with educational relations conducted by Indonesian students while studying in the middle east, until Indonesia became one of the countries that recognised the independence of Palestine on 15 November 1988 in Algeria. The relationship continues until now as seen from Indonesia's policies that are always on the Palestine side in the midst of the Palestine-Israel conflict. Many policies and assistance provided by Indonesia for Palestine in the fight for Palestine rights and independence ranging from political, socio-cultural, humanitarian assistance, as well as education. In fact, Indonesia also voiced peace efforts for Palestine in various forums, one of which was in the UN forum.